Longer durations of antitumour necrosis factor treatment are associated with reduced risk of cardiovascular events in patients with rheumatoid arthritis. Issue 1 (21st May 2015) - Nurmohamed, Michael; Bao, Yanjun; Signorovitch, James; Trahey, Alex; Mulani, Parvez; Furst, Daniel E
Abstract : Objective: To assess the effects of treatment with antitumour necrosis factor (TNF) agents, methotrexate, or other non-biological disease-modifying antirheumatic drugs (DMARDs) on cardiovascular event risks among patients with rheumatoid arthritis (RA). Methods: We conducted a retrospective study using data from the MarketScan claims database. Patients with RA with ≥1 prescription for an index drug were included. Each patient's use of an index drug was calculated cumulatively as a time-varying exposure. The incidence of cardiovascular events among patients with RA was determined. Associations between drug exposures and occurrence of cardiovascular events were assessed with Cox proportional hazards models. Results: Of 113 677 patients identified, 35.8%, 41.1% and 23.1% received anti-TNF agents, methotrexate and other DMARDs, respectively. Patients were treated for an average of 7.6 months; 2138 patients (1.9%) had a cardiovascular event following their index prescription. Each additional 6 months of anti-TNF therapy use versus non-use reduced the risk (HR; 95% CI) for any cardiovascular event by 12% (0.88; 0.81 to 0.95, p=0.002). Anti-TNF therapy was associated with a 13% and 12% reduction in cardiovascular events in patients aged ≥50 years (0.87; 0.80 to 0.95, p=0.002) and in those without prior methotrexate use (0.88; 0.78 to 0.99, p=0.04), respectively. Cumulative use of 1, 2 or 3 years of anti-TNF therapy versus non-use is expected to reduce cardiovascular event risks by 21%, 38% and 51%, respectively. Conclusions: Anti-TNF therapy was associated with a significantly lower risk of cardiovascular events among patients with RA, older patients with RA and patients without prior exposure to methotrexate.